Bibliometrics Analysis of Green Accounting Research - Dwianika, Agustine; Purwanto, Edi; Suyoto, Yohanes Totok; Pitaloka, Endang (International Journal of Energy Economics and Policy, 2024)
This research delves into Green Accounting, which integrates environmental considerations into traditional accounting practices. Green Accounting has garnered significant attention in the context of heightened global ecological awareness and sustainability efforts. The study examines the trends in Green Accounting publications, investigating various aspects such as subject areas, types of publications, and international dissemination. The objectives encompass analyzing publication trends from 1992 to mid-2023 and identifying influencing factors, exploring the implications of different publication types, revealing the significance of dominant subject areas, recognizing key international channels for dissemination, making global comparisons, acknowledging prominent authors' contributions, examining affiliations and roles of authors, and uncovering prevalent themes in Green Accounting publications. The methodology involves employing bibliometric analysis utilizing Scopus and VOSviewer tools to discern patterns and advancements in Green Accounting. The findings demonstrate fluctuations driven by environmental concerns, policy shifts, funding availability, and industry involvement. Dominant article types highlight interdisciplinary green economic engagement focusing on economic and ecological aspects. The research identifies global contributions to Green Accounting from developed and developing nations, driven by notable authors such as Cairns, Bartelmus, and Markandya, and spanning diverse affiliations like Universite McGill and the University of Bath, showcasing international interdisciplinary collaboration. Themes encompass environmental accounting, economics, corporate social responsibility, sustainable development, finance, and align with the Sustainable Development Goals. The study's novelty lies in its comprehensive analysis of Green Accounting's landscape, shedding light on its development, global involvement, and influences, thus providing valuable insights for stakeholders, policymakers, and researchers to advance sustainable practices. The implications underscore the need for ongoing research to address ecological challenges through Green Accounting, utilizing the understanding of trends, subject areas, and global engagement to formulate greener strategies, fostering collaboration among authors and affiliations, and enhancing overall awareness for facilitating sustainable development progress.